GE_GERICHTE P/16063/2020 vom 22. Juli 2021 - GE Cour de justice (2021)
PLAINTE PÉNALE;SOUPÇON;DOMMAGE DIRECT;DÉLIT CONTINU;SOUSTRACTION D'UNE CHOSE MOBILIÈRE;CORRUPTION;PERSONNE PRIVÉE | CP.30; CPP.310